An efficient and effective energy harvesting system using surface micromachined accelerometer - Thiru Gomathi; Maflin Shaby (Institute of Advanced Engineering and Science, 2022)
In many of the electronic devices the major role is performed by micro-electro-mechanical systems (MEMS). The electronics field has a vast application where in MEMS contribution to this field is very much greater. The electronics has a greater application in the area of micro-electro-mechanical systems which has greater applications in biomedical, electronics. The capacity, sensitivity in the power and its size helps MEMS for various different applications in different fields. If a device has a greater resonant frequency which can also be used in all frequencies that is at normal frequencies wider bandwidth, then also the MEMS fabrication can be done. A surface micromachined accelerometer is analyzed which can be used for generating energy from the environment. The characteristic feature is analyzed for the surface micromachined accelerometer. A surface micromachined accelerometer is simulate with a geometry of 3 space dimensions with a domain number of 120 whose number of boundaries are 838 which contains 1733 number of edges with 1076 vertices. The surface micromachined accelerator with all these specifications is simulate using COMSOL and the performance has been analyzed for various parameters namely frequency, acceleration and load impedance. The results show that energy has been harvested using the surface micromachined accelerometer.